2017
DOI: 10.1093/jac/dkx020
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antifungal activities of T-2307, a novel arylamidine, against Cryptococcus gattii: an emerging fungal pathogen

Abstract: T-2307 shows excellent in vitro and in vivo antifungal activities against C. gattii and would be a promising new candidate for the treatment of cryptococcosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Interestingly, brain fungal burden was significantly reduced in mice treated with T-2307 at 3 mg/kg (4.16 log 10 CFU/g) and caspofungin (2.51 log 10 CFU/g) versus untreated control (6.31 log 10 CFU/g) (P Յ 0.01). Previous studies have demonstrated reductions in brain and ocular tissue fungal burden in mice infected with Cryptococcus gattii and Candida albicans, respectively, and treated with T-2307 (10,11). In the current study, there was also a clear relationship between fungal burden and survival, as treated mice that survived to the day 21 endpoint had lower kidney and brain fungal burden compared to those that succumbed to infection.…”
supporting
confidence: 66%
“…Interestingly, brain fungal burden was significantly reduced in mice treated with T-2307 at 3 mg/kg (4.16 log 10 CFU/g) and caspofungin (2.51 log 10 CFU/g) versus untreated control (6.31 log 10 CFU/g) (P Յ 0.01). Previous studies have demonstrated reductions in brain and ocular tissue fungal burden in mice infected with Cryptococcus gattii and Candida albicans, respectively, and treated with T-2307 (10,11). In the current study, there was also a clear relationship between fungal burden and survival, as treated mice that survived to the day 21 endpoint had lower kidney and brain fungal burden compared to those that succumbed to infection.…”
supporting
confidence: 66%
“…The efficacy of T-2307 was confirmed in murine models of cryptococcosis: at 0.1 mg/kg, T-2307 significantly delayed mortality in mice infected by C. neoformans when compared with the untreated group, and T-2307 exhibited a superior protective effect compared to AMB at similar treatment regimens [64]. Administration of T-2307 alone at 2 mg/kg/day significantly reduced viable cell counts in the lungs and brain of mice infected by C. gattii and the results were similar to standard treatments [65].…”
Section: T-2307mentioning
confidence: 60%
“…T-2307 is a novel arylamidine derivative with broad-spectrum of action and potent in vitro and in vivo activities, that acts by selectively disrupting mitochondrial function in yeasts [63]. The antifungal activity for C. neoformans was observed at MIC ranging from 0.0039 to 0.0625 µg/mL [64], and for C. gattii at 0.0078-0.0625 µg/mL [65]. The efficacy of T-2307 was confirmed in murine models of cryptococcosis: at 0.1 mg/kg, T-2307 significantly delayed mortality in mice infected by C. neoformans when compared with the untreated group, and T-2307 exhibited a superior protective effect compared to AMB at similar treatment regimens [64].…”
Section: T-2307mentioning
confidence: 99%
“…T2307 is an allylamine that displays significant anticryptococcal activity in vitro and in vivo by collapsing mitochondrial membrane potential. It has very potent anticryptococcal activity against C. gattii in non-immunocompromised murine models of cryptococcosis [ 29 ].…”
Section: Future Therapeutic Options and Directionsmentioning
confidence: 99%